2015
DOI: 10.1016/j.aprim.2014.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Población potencialmente excluida de cobertura sanitaria con el Real Decreto 16/2012 y sus repercusiones sanitarias: la experiencia desde la Cataluña Central

Abstract: The results of the study suggests that this legislative measure does not seem to be justified for medical or economic reasons. It could also cause public health problems and contribute to the risk of social fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
2
5
0
3
Order By: Relevance
“…Las políticas sociales ante la crisis afectan al Sistema de Salud directamente y con ello se reducen presupuestos destinados en sanidad, recursos, personal y actividad preventiva. Las medidas tomadas tienen consecuencias negativas para todo el grupo de población y la salud pública en general (8) .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Las políticas sociales ante la crisis afectan al Sistema de Salud directamente y con ello se reducen presupuestos destinados en sanidad, recursos, personal y actividad preventiva. Las medidas tomadas tienen consecuencias negativas para todo el grupo de población y la salud pública en general (8) .…”
Section: Resultsunclassified
“…España, país desarrollado, alberga un sistema sanitario de carácter público, prestando sus servicios a toda la población, cuya base es garantizar la igualdad en el acceso y la utilización de los servicios a toda la ciudadanía (7,8) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…11,12 A study by Á lamo-Junquera and colleagues found that the prevalence of those excluded from accessing the health care system was 0.53% among those who did not have an IHC in Catalonia. 13 The Autonomous Communities that are part of Spain have reacted in varied ways to this law. This has created inequalities and inconsistencies regarding who is eligible for health care access, depending on the Autonomous Community of residency.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the frequency of consultation with any type of physician was higher in 2014 than in 2009, an increase that was greater in the immigrant population. According to some authors, the regional governments did not apply the measure implemented by the central government, and this could be reason for the findings in the immigrant population [17,18]. Nevertheless, the native-born population knows better than immigrants how the healthcare system works, and this knowledge may help them to avoid entering the health system through the family physician.…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%